Gender and Situational Variation of Pitch Dynamism in Thai Speakers - Wu, Athit (NIDA Journal of Language and Communication, 2025)
Human physiology confirms that male and female voices exhibit different fundamental frequencies (F0) intrinsically. However, whether the use of F0 in everyday speech differs between males and females remains contentious. Perceptually, female speech is often considered more fluctuating, swoopy, and melodic compared to male speech. This study aims to investigate this issue by revisiting methods of measuring F0 in utterances to determine whether the differences between male and female speakers mentioned above exist. Pitch dynamism, defined as a two-dimensional value (x, y) comprising pitch perturbation and pitch variance, has been selected as the acoustic variable. Additionally, this study examines the influence of situational context on utterance F0. Recordings were collected from six native Thai students (three males and three females), involving both reading speech and spontaneous speech. The results indicate a significant difference in utterance F0 between male and female speakers, with pitch variance serving as the primary distinguishing cue. Furthermore, the analysis reveals that situational context significantly affects the realization of utterance F0.